Boundaries Through the Prism of Post-secondary and Professional Orientation: The Views of Young Québec Adults of Immigrant Background - Darchinian, Fahimeh; Magnan, Marie-Odile (Journal of Ethnic and Cultural Studies, 2020)
Based on our collection of life stories (n = 25), our qualitative study seeks to better understand, after the fact, how young, immigrant-background adults in Québec negotiate ethnocultural boundaries through their post-secondary and professional orientation experiences, particularly in terms of linguistic choices. The analyses highlight the strengthening of boundaries within Québec’s educational institutions and workplaces. The results expose different examples of racism experienced by young adults in their relations with the Québec francophone majority that led them to integrate into English-language post-secondary education and workplaces. In addition, young adults from “black” and “Arabic” minorities more frequently report racist attitudes from francophone Quebecers.